a) The linear equation is Y=mX+c

∵ the Y intercept is (0,6)

∴ c=6

Substitute to get m

∵m*7+6=0

∴ m=-6/7

∴ X^2= -6/7 ln y+ b

ln y=-7/6 (x^2-6)

Then we can express y in terms of x

y=e^(-7/6 (x^2-6))

b) Substitute 1 into the equation

ln y=-7/6 (x^2-6)

∴ln (1)= -7/6 (k^2-6)

0=-7/6 (k^2-6)

k1=√6 k2=-√6 (rejected ∵it can't be negative)

The working and answer is good.

ReplyDeleteGenerally well explained, but there are some vague points. In the part where they substitute to get m, its not very clear which coordinates were substituted in. It was also not very clear why k2 was rejected simply because it was negative. Does it not make sense if it is substituted back into the equation? or does it yield an imaginary/undefined result?

ReplyDeleteThe steps and explanation are a little confusing and the last part lacked justification . ( Why negative is rejected)

ReplyDelete